2019
DOI: 10.1136/bmjopen-2019-030279
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising precision public health

Abstract: As currently conceived, precision public health is at risk of becoming precision medicine at a population level. This paper outlines a framework for precision public health that, in contrast to its current operationalisation, is consistent with public health principles because it integrates factors at all levels, while illuminating social position as a fundamental determinant of health and health inequities. We review conceptual foundations of public health, outline a proposed framework for precision public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 74 publications
1
41
0
Order By: Relevance
“…Finally, in the current context of declining life expectancy and increasing inequalities in the UK,50 it is concerning that PPH approaches are being strongly promoted as solutions 51. We agree with the recent commentary by Olstad and McIntyre that PPH could benefit, conceptually and practically, from a refocus on the upstream social determinants of health 52. In the meantime, while evidence for sound policy and practice is still being sought, we consider Horton’s diagnosis of ‘pilotitis’ premature 1…”
Section: Discussionsupporting
confidence: 71%
“…Finally, in the current context of declining life expectancy and increasing inequalities in the UK,50 it is concerning that PPH approaches are being strongly promoted as solutions 51. We agree with the recent commentary by Olstad and McIntyre that PPH could benefit, conceptually and practically, from a refocus on the upstream social determinants of health 52. In the meantime, while evidence for sound policy and practice is still being sought, we consider Horton’s diagnosis of ‘pilotitis’ premature 1…”
Section: Discussionsupporting
confidence: 71%
“…The main thrust of RoadMApp intervention in global health is to improve community level health following precision public health principles. Central to the notion of precision public health is the concept of identifying speci c risk factor pro les that confer vulnerability to poor health [33]. Identifying that long travel times to seek health care is a risk factor motivated the development of the RoadMApp and subsequent guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, some have suggested that PPH could divert attention away from the broader determinants of health towards clinical concepts, which tend to be measured with greater accuracy [13]. For example, the social determinants of health, such as social status, are generally not measured well, so they may play a limited role in characterizing populations and identifying optimal interventions [7,14]. Concerns have also been raised about attempts to use genomic data in PPH, due to the limited availability of such data for many sub-populations and the usually small effect size at a population scale compared to other determinants of health [7].…”
Section: Precision Public Healthmentioning
confidence: 99%
“…While the concept of PPH is gaining traction and initial research results in global health and infectious diseases are promising, there remain many opportunities for informatics research in this area. From a measurement or diagnostic perspective, widely adopted frameworks for measuring non-clinical concepts, such as social position [14] are needed to consistently classify populations for precisely identifying interventions [27]. These advances in measurement, especially through the use of new and large data sources, have some overlap with the concept of digital epidemiology [28].…”
Section: Precision Public Healthmentioning
confidence: 99%